Bacterial astaxanthin: production and application in aquaculture - a review - Lien, Nguyen Thi Kim; Lan, Nguyen Ngoc; Thoa, Nguyen Kim; Dieu Phuong, Nguyen Thi; Huy, Nguyen Quang; Hoang, Nguyen Huy (Vietnam Journal of Biotechnology, 2018)
Astaxanthin is red or pink pigment that found in crustaceans and marine animals. Astaxanthin plays an important role in enhancing the commercial value, the reproductivity and survivability of aquatic species. Due to crustaceans and marine animals are unable to self-synthesize astaxanthin, the demand for astaxanthin especially natural astaxanthin added to the food for aquaculture are increasing. Natural astaxanthin sources from algae, yeast and bacteria are being used in industrial production. However, astaxanthin from bacteria has the advantage of being easier to absorb than algae and yeast. Therefore, astaxanthin biosynthesis by bacteria are being very noticeable. Many bacterial strains are capable of producing astaxanthin such as Paracoccus spp., Agrobacterium spp., Sphingomonas spp., Pseudomonas spp., Halobacterium spp.... Among these, Paracoccus carotinifaciens is one of the most studied and used species in astaxanthin production. In this review, we summarize information about the role and situation using of astaxanthin in aquaculture. Especially, we focus on the astaxanthin from bacteria in aquaculture to improve color of aquatic species such as ornamental fish, rainbow trout, and shrimp in the world and Vietnam. Besides that, the progress to enhance astaxanthin production such as genetic engineering, gene mutations, as well as optimization of fermentation conditions are also discussed in this article. These are useful information for the development and application of astaxanthin from bacteria in aquaculture.